Aesthetics of Displacement Turkey and its Minorities on Screen - Koksal, Ozlem (Bloomsbury Academic, 2016)
Looking at films that represent the experience of displacement in relation to Turkey's minorities, Aesthetics of Displacement argues that there is a particular aesthetic continuity among the otherwise unrelated films. Ozlem Koksal focuses on films that bring taboo issues concerning the repression of minorities into visibility, arguing that the changing political and social conditions determine not only the types of stories told but also the ways in which these stories are told.
Description based on print version record.
KU Select 2019: HSS Backlist Books
Keywords: Performing Arts / Film / History & Criticism; Performing Arts / Film; Performing arts; Electronic books